F14 8OHdG is not a biomarker for Huntington's disease; lessons for future biomarker studies. (29th August 2012) - Borowsky, B; Warner, J; Matson, W; Johnson, H; Durr, A; Roos, R; Tabrizi, SJ; Leavitt, B; Becker, C; Tobin, A; Schulman, H
Abstract : Background: No candidate blood, CSF or urine biomarkers for HD have been clinically validated. 8-hydroxy-deoxy-guanosine (8OHdG) has been proposed as a candidate biomarker. Increased levels of 8OHdG have been reported in post-mortem brains 1 2 and in serum, 3 leucocytes 4 and plasma 5 of HD patients. All of the published studies on 8OHdG utilised a liquid chromatography electrochemical array (LCECA) assay. Aims: To evaluate the potential of plasma 8-OHdG as a biomarker of HD state or progression and to develop a general set of procedures to test potential biomarkers. Methods: We established a new liquid chromatography-mass spectrometry (LCMS) assay for 8OHdG and used it to measure 8OHdG levels in a cross-sectional plasma collection from the PREDICT-HD study. Next, longitudinal plasma samples taken 24 months apart from 160 TRACK-HD subjects, along with control plasma with added ("spiked") 8OHdG, were sent blindly to two laboratories for measurement of 8OHdG using either the LCECA or the LCMS assay. Results: We found no differences in 8OHdG levels between controls, premanifest HD and clinically diagnosed HD subjects from the PREDICT-HD study using the LCMS assay. A blinded head to head comparison showed the LCMS assay to be more accurate than the LCECA assay at measuring 8OHdG from spiked control plasma. Both assays were consistent in demonstrating no cross sectional differences in plasma 8OHdG between TRACK-HD controls, premanifest HD and early symptomatic HD subjects, and no longitudinal changes in any of the disease groups over 24 month. Conclusions: Plasma concentration of 8-OHdG should not be considered a potential biomarker of disease state or disease progression in HD. To avoid the errors that have plagued such analyses, studies of all putative biomarkers should employ (1) blinded sample analyses; (2) verification of measurements by independent analytic methods; (3) standard curves; and (4) collection and storage of biological fluids under strict quality control. References: 1. Browne SE, Bowling AC, MacGarvey U, et al. Oxidative damage and metabolic dysfunction in Huntington's disease: selective vulnerability of the basal ganglia. Ann Neurol 1997;41 :646–53. 2. Polidori MC, Mecocci P, Browne SE, et al. Oxidative damage to mitochondrial DNA in Huntington's disease parietal cortex. Neurosci Lett 1999;272 :53–6. 3. Hersch SM, Gevorkian S, Marder K, et al. Creatine in Huntington disease is safe, tolerable, bioavailable in brain and reduces serum 8OH2'dG. Neurology 2006;66 :250–2. 4. Chen C, Wu Y, Cheng M, et al. Increased oxidative damage and mitochondrial abnormalities in the peripheral blood of Huntington's disease patients. Biochem Biophys Res Commun 2007;359 :335–40. 5. Long JD, Matson WR, Juhl AR, et al ; PREDICT-HD Investigators and Coordinators of the Huntington Study Group. 8OHdG as a marker for Huntington disease progression. Neurobiol Dis 2012;46 :625–34.